The daughter's tale [compact disc, unabridged] : a novel - Correa, Armando Lucas, 1959- (Simon & Schuster Audio, 2019)
New York City, 2015: Elise Duval, eighty-years-old, receives a phone call from a woman bearing messages from a time and country that she's long forgotten. Elise is forever changed when the woman arrives with letters from her mother written in German during the war, unravelling more than seven decades of secrets. Based on true events, it chronicles one of the most harrowing atrocities perpetrated by the Nazis during World War II: the 1944 massacre of a small, idyllic village in the south of France.